1998
DOI: 10.1074/jbc.273.47.30870
|View full text |Cite
|
Sign up to set email alerts
|

Sp1-binding Elements in the Promoter of RAGE Are Essential for Amphoterin-mediated Gene Expression in Cultured Neuroblastoma Cells

Abstract: Receptor for AGE (RAGE) and the polypeptide amphoterin are highly expressed and co-localized in neurons of the developing central nervous system of the rat. In vitro, the interaction of amphoterin with neuronal RAGE induces neurite outgrowth. We tested the hypothesis that interaction of amphoterin with neuronal cells enhances RAGE expression, thereby providing a mechanism by which amphoterin-mediated regulation of RAGE might contribute to promotion of neurite growth and spreading. Incubation of cultured neurob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…Interestingly, the analysis of the promoter region of RAGE gene revealed the presence of two functional NF-B-binding sites (46) suggesting a possible autoregulatory loop in the regulation of RAGE expression. However, when this manuscript was under preparation a finding was published (47) showing that amphoterin-induced increase in RAGE expression is mediated by binding of amphoterin to RAGE resulting in Sp1 activation rather than activation of NF-B. Soluble amphoterin was used in their study, whereas we have used matrix-bound amphoterin.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the analysis of the promoter region of RAGE gene revealed the presence of two functional NF-B-binding sites (46) suggesting a possible autoregulatory loop in the regulation of RAGE expression. However, when this manuscript was under preparation a finding was published (47) showing that amphoterin-induced increase in RAGE expression is mediated by binding of amphoterin to RAGE resulting in Sp1 activation rather than activation of NF-B. Soluble amphoterin was used in their study, whereas we have used matrix-bound amphoterin.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that enhanced MPO activity within the first hour after injury, induced at least in part by polymorphonuclear leukocytes attracted immediately to the injured arterial segment, triggers oxidant stress (39), thereby providing a definitive mechanism leading to formation of AGEs (38)(39)(40). We hypothesize that once formed, AGE ligands of the receptor likely stimulate enhanced expression of RAGE itself (55,56). In parallel, studies have suggested that acute injury, as well as proinflammatory stimuli, may enhance expression of S100/calgranulin ligands of RAGE (34-37), thus providing a mechanism for enhanced RAGE expression, as well.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE expression increases in circumstances when ligands, such as AGEs, and inflammatory mediators accumulate (106,116). Because the RAGE promoter contains multiple functional NF-κB and SP-1 transcription factor-binding sites (117,118), ligands and proinflammatory cytokines can promote the expression of RAGE, potentially triggering a receptor-dependent autoinflammatory loop.…”
Section: The Receptor For Advanced Glycation End Products (Rage)mentioning
confidence: 99%